Pengendalian Hama Daun Tanaman Sawi (Brassica juncea L.) Di Kecamatan Landasan Ulin Utara - Efrian Maulana Fadani; Samharinto Samharinto; Salamiah Salamiah (Universitas Lambung Mangkurat, 2026)
Vegetables have become the main food ingredient in healthy life in Indonesia. Vegetable commodities with selling value and have good business opportunities, one of which is green mustard plants (Brassica juncea L.). Green mustard plants is kind of vegetables that are easily cultivated, in their implementation can quickly produce because this plant has a relatively short lifespan. Farmers always strive to get the most optimal results of green mustard crop production, but of course there are obstacles in the process, one of which is the attack of pests on plants. In lowland areas in South Kalimantan, such as Landasan Ulin area, due to pest attacks on green mustard plants, especially P. xylostella mustard caterpillars can cause damage up to 100% in the dry season, if control measures are not taken (Gazali, 2011). The farmers in general still uses chemical pesticides to control pests on green mustard plants. This study aims to study how to control pests on green mustard plants in three locations in Landasan Ulin Utara District, carried out for two months starting from June-July 2023, in the villages of Sukamara, Sukamaju and Syamsuddin Noor, Landasan Ulin Utara, Banjarbaru. The method of this study is non-experimental surveys and interviews with farmers. Each village took one green mustard planting location and interviewed 5 farmers each village who worked on the planting land.